ANALISIS ETIKA MEROKOK MAHASISWA PPKN ANGKATAN 2022 DI LINGKUNGAN KAMPUS UNIVERSITAS JAMBI - Silvia, Fira; Ichsan, Muhammad; Dewi, Nurmalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the smoking ethics of Civic Education students of the class of 2022 at Universitas Jambi campus based on Kohlberg's theory of moral development. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving seven informants consisting of three smoking students, two non-smoking students, the Civic Education Program Coordinator, and a security officer. Data analysis used the Miles and Huberman model: data reduction, data display, and conclusion drawing, validated through triangulation. Results show that the smoking ethics of PPKn class of 2022 students ranges from pre-conventional to conventional levels. At the pre-conventional level, compliance with the Smoke-Free Zone policy is situational and authority-dependent. At the conventional level, students follow group norms informally, using areas such as the student cooperative and the Faculty of Teacher Training and Educationparking lot as informal smoking zones. Post-conventional indicators were practically absent. Contributing factors are divided into internal factors (nicotine addiction, academic stress, social identity motivation, and low moral reasoning) and external factors (peer pressure, weak the Smoke-Free Zone enforcement, minimal no-smoking signage, seniority culture, and absence of intervention programs). These findings suggest the need for stronger the Smoke-Free Zone implementation, more contextual character education, and structured stress management programs.